PERANCANGAN APLIKASI UNTUK PERALATAN PEMANTAU SUHU MENGGUNAKAN RADIO FREQUENCY (RF) - Wahid Kurniawan; Denny Dermawan; Yuliani Indrianingsih (Institut Teknologi Dirgantara Adisutjipto, 2012)
Temperature is a part of the natural condition that related to human activities. Many human activity is affected by temperature fluctuation factors. For example, in this case is a temperature monitoring at these broiler farms and database monitoring center computer. Room temperature for places are two examples of the human activities that the temperature factor is concerned. Until now, time temperature monitoring activity is done manually, thus it is need a monitoring tool that can be viewed from the computer interface.To save time and cost, application for temperature monitoring equipment is made so that the results can be seen from a distance. The applications are user friendly, so users can easily find out the temperature value.Application for temperature monitoring equipment is useful to support the activities of monitoring the temperature. From the experimental results, the application for temperature monitoring equipment that uses radio frequency results can be viewed from a computer interface, so as to streamline the performance of temperature monitoring.